A novel and practical conceptual framework to support Lean Six Sigma deployment in manufacturing SMEs. (18th August 2022) - Alexander, Paul; Antony, Jiju; Cudney, Elizabeth
Abstract : The purpose of this paper is to review the existing Lean, Six Sigma and Lean Six Sigma implementation models and frameworks and present a new conceptual framework designed specifically for manufacturing small- and medium-sized enterprises (SME). This paper details the thorough review of 20 existing deployment models and frameworks for Lean, Six Sigma, and Lean Six Sigma. The systematic review demonstrates there is a need for a Lean Six Sigma deployment model designed specifically for manufacturing SMEs. By identifying the weaknesses and strengths of the existing frameworks and models, a new conceptual deployment model is presented for manufacturing SMEs. This research demonstrates the requirement for a Lean Six Sigma deployment framework specifically for manufacturing SMEs. The existing models do not acknowledge that SMEs have their own dynamics and characteristics; therefore, all organisations cannot be considered homogeneous in nature. A new conceptual deployment model is presented which is easy to follow and user-friendly in nature. Some of the positive aspects of the new conceptual model that has its antecedents in previous models were applicable. The framework presented provides manufacturing SMEs increased utility by providing a framework for Lean Six Sigma deployment designed specifically for manufacturing SMEs. The framework provides a clear guide for deployment and an overview of the process steps necessary for proper implementation. The model presented is adaptable in nature and promotes the execution of strategy based on the capabilities and skill set of the organisation. The paper presents an original conceptual deployment framework for Lean Six Sigma for manufacturing SMEs. The model demonstrates a robust practical framework for use by SMEs of varying capabilities, strengths, and weaknesses. This should increase the efficacy of LSS deployment and add utility to organisations.